Compliance with Standard Precautions: A long way ahead - M Jawaid; M Iqbal; S Shahbaz (Tehran University of Medical Sciences, 2009)
Background: To find out the knowledge, attitude and compliance with standard precautions among doctors working in a tertiary care hospital. Methods: The cross sectional study was conducted during October 2006 in the form of self reporting questionnaire. The questionnaire included question about duration of clinical experience, Hepatitis B Virus vaccination and its antibody titer, knowledge and compliance of Centre for Disease Control (CDC) standard precaution guidelines. They were further asked about reasons for non compliance. Results: Total 120 doctors participated in this study which includes 60% interns, 34.2% residents and 5.8% consultants. Total 95% respondents were vaccinated against Hepatitis B virus but only 27.4% knew their antibody titers.  Majority of the doctors, 52.5% didn't know any thing about Centres for Disease Control guideline for standard precautions while 40% of the respondent had some idea and only 7.5% knew them well. Among responders 56.7% changed gloves for each patient and only 39.2% washed hand in between examining patients. Most of the doctors 58.3% said they always wear apron while dealing with patients while 20% wear only when dealing with high risk patients. Protective goggles were not used by any of our respondent. The reasons given for non-compliance included non-availability of protective modalities by 58.3% while 20% were of the opinion that it's not practical. Conclusion: The knowledge attitude and compliance among doctors towards standard precautions is in-adequate. Availability of supplies and awareness programmes for these standard precautions are recommended for better compliance.